Child Labour and Health During the Industrialization in Western Europe with Special Reference to Prussia - Vögele , Jörg Peter; Liczbińska, Grażyna (Studia Historiae Oeconomicae, 2023)
Child labour is a controversial issue both in present day as well as in past societies. In historical perspective, studies focus on the factory labour of children during the industrialization process. On the one hand, its contribution to the family income is mentioned as a potential positive effect on the living standard of the whole family, on the other hand reference is made to the permanent health risks for children working in the factories. Using qualitative sources, there were contemporary testimonies supporting both views. The present paper, therefore, uses a rather quantitive approach referring to the number of working days lost due to illness, anthropometric indicators such a height and weight, the results of draft examinations as well as mortality differences and cause-of-death rates from “accidents” in urban and rural areas during the nineteenth century. Available data do not provide clear evidence of direct harmful effects of child labour; many indications point to a neutral or even positive effect.